1997
DOI: 10.1523/jneurosci.17-14-05480.1997
|View full text |Cite
|
Sign up to set email alerts
|

Functional Specificity of Long-Range Intrinsic and Interhemispheric Connections in the Visual Cortex of Strabismic Cats

Abstract: The development of both long-range intracortical and interhemispheric connections depends on visual experience. Previous experiments showed that in strabismic but not in normal cats, clustered horizontal axon projections preferentially connect cell groups activated by the same eye. This indicates that there is selective stabilization of fibers between neurons exhibiting correlated activity. Extending these experiments, we investigated in strabismic cats: (1) whether tangential connections remain confined to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 94 publications
8
85
1
Order By: Relevance
“…These resembled closely the activation patterns revealed with 2-DG after similar stimulation conditions (Schmidt et al, 1997b). As expected for strabismic animals (e.g.…”
Section: Layout Of Ocular Dominance Columnssupporting
confidence: 87%
See 3 more Smart Citations
“…These resembled closely the activation patterns revealed with 2-DG after similar stimulation conditions (Schmidt et al, 1997b). As expected for strabismic animals (e.g.…”
Section: Layout Of Ocular Dominance Columnssupporting
confidence: 87%
“…Consist-ent with previous electrophysiological and anatomical experiments (i.e. Hubel & Wiesel, 1965;Löwel & Singer, 1992;König et al, 1993;Schmidt et al, 1997b) our optical imaging data thus give no indication of a disadvantage of the deviated compared with the non-deviated eye in divergently squinting cats (Figs 1-4).…”
Section: Layout Of Ocular Dominance Columnssupporting
confidence: 86%
See 2 more Smart Citations
“…Therefore, our study reveals that functional characteristics of visual callosal transfer might be affected differentially by early strabismus, depending on the rule governing the connections subserving them. Based on a series of elegant experiments combining optical recording, deoxyglucose labelling and retrograde tracing, Schmidt et al (1997aSchmidt et al ( , 1997b concluded that long-range corticocortical connections ± intrahemispheric as well as interhemispheric ± are selected during development according to perceptual grouping criteria and thereafter link domains of similar ocularity or orientation selectivity. These connections are considered to be the substrate for long-range, stimulus-speci®c synchronization of visual responses, a phenomenon that is proposed to serve as a mechanism for dynamic tagging of visual responses, as belonging to neuronal assemblies (reviewed in Singer & Gray, 1995).…”
Section: Effects Of Strabismus On Callosal Recipient Neuronsmentioning
confidence: 99%